40 years of 416-bis. The origins of the Rognoni-La Torre Law (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
Forty years after the Rognoni-La Torre law, a reflection is proposed on the historical-political context in which the law was enacted, the pressures that led to its approval, its historical significance, and the aspects of continuity between countering the Mafia and countering terrorism. Particular attention is dedicated to the political confrontation and its impact on the measure. The intent is to introduce the reader to the analysis of the foundational texts of the law, which are reported hereafter.
Keywords: La Torre, mafia, terrorismo, dalla Chiesa, Rognoni, 416-bis